2011
DOI: 10.1186/1745-6673-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in asbestos-exposed workers, a systematic review and meta-analysis

Abstract: BackgroundA continuing controversy exists about whether, asbestos exposure is associated with significant lung function impairments when major radiological abnormalities are lacking. We conducted a systematic review and meta-analysis in order to assess whether asbestos exposure is related to impairment of lung function parameters independently of the radiological findings.MethodsMEDLINE was searched from its inception up to April 2010. We included studies that assessed lung function parameters in asbestos expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 66 publications
3
16
0
4
Order By: Relevance
“…A subgroup analysis designed to compare pulmonary function in those asbestos‐exposed subjects with and without pleural plaques revealed significant decrease in FVC, and a trend for decrease in FEV 1, in those with isolated pleural plaques. This result is consistent with multiple prior studies that demonstrate lower FEV 1 and FVC in cohorts with high levels of asbestos exposure and presence of pleural plaques [Jarvholm and Sanden, ; Oliver et al, ; Bourbeau et al, ; Lilis et al, ; Wilken et al, ; Kopylev et al, ]. Lockey and colleagues [Lockey et al, ] reported a relationship between cumulative fiber exposure and localized pleural thickening at lifetime exposure levels 3–10 times less than the 45‐year working lifetime U.S. Occupational Safety and Health Administration standard of 4.5 fiber‐year/cm 3 for commercial asbestos exposure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A subgroup analysis designed to compare pulmonary function in those asbestos‐exposed subjects with and without pleural plaques revealed significant decrease in FVC, and a trend for decrease in FEV 1, in those with isolated pleural plaques. This result is consistent with multiple prior studies that demonstrate lower FEV 1 and FVC in cohorts with high levels of asbestos exposure and presence of pleural plaques [Jarvholm and Sanden, ; Oliver et al, ; Bourbeau et al, ; Lilis et al, ; Wilken et al, ; Kopylev et al, ]. Lockey and colleagues [Lockey et al, ] reported a relationship between cumulative fiber exposure and localized pleural thickening at lifetime exposure levels 3–10 times less than the 45‐year working lifetime U.S. Occupational Safety and Health Administration standard of 4.5 fiber‐year/cm 3 for commercial asbestos exposure.…”
Section: Discussionsupporting
confidence: 89%
“…The American Thoracic Society, in considering pulmonary function changes due to asbestos‐related pleural plaques, concluded that studies of large cohorts showed a significant 5% reduction in FVC attributable to the plaques [ATS Statement, ]. Wilken and colleagues [Wilken et al, ] performed a systematic review and meta‐analysis of 9,921 workers exposed to asbestos and found a statistically significant reduction in FVC in those without radiological changes [94.9% predicted (95%CI 92.9–96.9)], those with pleural fibrosis [87.1% predicted (95%CI 83.9–90.4)], and asbestosis [84.8% predicted (95%CI 80.8–88.8)].…”
Section: Discussionmentioning
confidence: 99%
“…Although the American Thoracic Society Statement41 addresses the relationship of chronic airway obstruction to asbestos exposure, the frequency and severity have been observed to be greater in the Libby cohort. Thus, contributions to significant airway obstruction decreased FEV 1 and/or low FEV 1 /FVC could arise from asbestos42 as well as smoking. Differences in DL CO were associated with gender, age, smoking history and radiographic findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is well‐known that exposure to all kinds of dusts results in a decrease in lung function. There is no reason to assume that this is different for asbestos exposure . The latter is especially clarified in the meta‐analysis of Wilken et al summarizing all available work, demonstrating a small, but statistically significant impairment in FVC, FEV 1 , and FEV 1 /VC in asbestos workers with normal chest X‐ray or Computed Tomography findings (see Figure and Table ).…”
Section: Commentmentioning
confidence: 99%